2019
DOI: 10.4103/1673-5374.253506
|View full text |Cite
|
Sign up to set email alerts
|

Tandem pore TWIK-related potassium channels and neuroprotection

Abstract: TWIK-related potassium channels (TREK) belong to a subfamily of the two-pore domain potassium channels family with three members, TREK1, TREK2 and TWIK-related arachidonic acid-activated potassium channels. The two-pore domain potassium channels is the last big family of channels being discovered, therefore it is not surprising that most of the information we know about TREK channels predominantly comes from the study of heterologously expressed channels. Notwithstanding, in this review we pay special attentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 158 publications
0
13
0
1
Order By: Relevance
“…Delayed rectified potassium voltage-gated channels, Kcnc2 and Kcng2 , play key roles in action potential shaping and consequently in nociception transmission and pain plasticity 45 . Kcnk1 8, a TWIK-related two-pore potassium channel is involved in regulating the resting membrane potential 68 , 69 and has been linked to migraine with aura pathogenesis 70 , 71 . Finally, we identified higher expression of Trpv4 in female TG sensory neuronal fractions and this ion channel plays an important role in pain sensitization that has been thoroughly studied 47 , 72 .…”
Section: Discussionmentioning
confidence: 99%
“…Delayed rectified potassium voltage-gated channels, Kcnc2 and Kcng2 , play key roles in action potential shaping and consequently in nociception transmission and pain plasticity 45 . Kcnk1 8, a TWIK-related two-pore potassium channel is involved in regulating the resting membrane potential 68 , 69 and has been linked to migraine with aura pathogenesis 70 , 71 . Finally, we identified higher expression of Trpv4 in female TG sensory neuronal fractions and this ion channel plays an important role in pain sensitization that has been thoroughly studied 47 , 72 .…”
Section: Discussionmentioning
confidence: 99%
“…TWIK-related K + channels (TREK-1, TREK-2, and TRAAK) are a mechano-gated subclass of K 2P channels, and are highly expressed throughout the nervous system (Talley et al, 2001) as well as in several nonneuronal tissues including cardiac and smooth muscles (Gurney and Manoury, 2009;Schmidt et al, 2014;Ma et al, 2018). TREK-1 in particular plays a central role in pain perception, neuroprotection, and cardiac rhythmogenesis (Alloui et al, 2006;Wiedmann et al, 2016;Lamas and Fernandez-Fernandez, 2019) and is considered a viable therapeutic target for treating depression (Heurteaux et al, 2006), atrial fibrillation (Lugenbiel et al, 2017), and hypermotility disorders of the gastrointestinal tract (Ma et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the K 2P channels, the presence of these channels in HUA is uncertain, and only Martin et al (2014) have reported the presence of mRNA from the TREK-1 and TRAAK channels. Increasing evidence shows a role for TREK channels in cardiac pathologies such as atrial fibrillation and heart failure [ 202 , 203 , 204 ]. TREK-1 channel openers include riluzole, chloroform, and diethyl ether.…”
Section: Clinical Importance and Medical Uses Of K + mentioning
confidence: 99%